High seroprevalence of SARS-CoV-2 in Burkina-Faso, Ghana and Madagascar in 2021: a population-based study - Struck, Nicole Sunaina; Lorenz, Eva; Deschermeier, Christina; Eibach, Daniel; Kettenbeil, Jenny; Loag, Wibke; Brieger, Steven A.; Ginsbach, Anna M.; Obirikorang, Christian; Maiga-Ascofare, Oumou; Sarkodie, Yaw Adu; Boham, Eric Ebenezer Amprofi; et al. (BMC public health, 2022)
The current COVID-19 pandemic affects the entire world population and has serious health, economic and social consequences. Assessing the prevalence of COVID-19 through population-based serological surveys is essential to monitor the progression of the epidemic, especially in African countries where the extent of SARS-CoV-2 spread remains unclear.